A comparison of calls subjected to a malpractice claim versus 'normal calls' within the Swedish Healthcare Direct: a case–control study. Issue 10 (3rd October 2014) - Ernesäter, Annica; Engström, Maria; Winblad, Ulrika; Holmström, Inger K
Abstract : Objectives: The purpose of this study is to compare communication patterns in calls subjected to a malpractice claim with matched controls. Setting: In many countries, telephone advice nursing is patients' first contact with healthcare. Telenurses' assessment of callers' symptoms and needs are based on verbal communication only, and problems with over-triage and under-triage have been reported. Participants: A total sample of all reported medical errors (n=33) during the period 2003–2010 within Swedish Healthcare Direct was retrieved. Corresponding calls were thereafter identified and collected as sound files from the manager in charge at the respective call centres. For technical reasons, calls from four of the cases were not possible to retrieve. For the present study, matched control calls (n=26) based on the patient's age, gender and main symptom presented by the caller were collected. Results: Male patients were in majority (n=16), and the most common reasons for calling were abdominal pain (n=10) and chest pain (n=5). There were statistically significant differences between the communication in the cases and controls: telenurses used fewer open-ended medical questions (p<0.001) in the cases compared to the control calls; callers provided telenurses with more medical information in the control calls compared to the cases (p=0.001); and telenurses used more facilitation and patient activation activities in the control calls (p=0.034), such as back-channel response (p=0.001), compared to the cases. Conclusions: The present study shows that telenurses in malpractice claimed calls used more closed-ended questioning compared to those in control calls, who used more open-ended questioning and back-channel response, which provided them with richer medical descriptions and more information from the caller. Hence, these communicative techniques are important in addition to solid medical and nursing competence and sound decision aid systems.